The war on drugs: destigmatizing drug use as a way forward - Ullase, Līga (Riga Graduate School of Law, 2023)
The aim of this thesis is to analyze why the war on drugs has been recognized as a failure by academics, policy makers and experts in the fields of drugs, psychiatry and economy and how to move forward and turn failure into a success by changing the approach. Firstly, to understand the basis of the world wide drug prohibition, it is necessary to cover the treaties that are the main building block of the multilateral efforts against drug use and trafficking. Secondly, it reviews how racism has impacted the policy makers thus created a stigma against drug users. Thirdly, the paper analyzes the anti scientific approach of drug scheduling and harms caused by alcohol and tobacco. And lastly, an extensive comparative analysis is provided on alternative drug policies provides a perspective that has inspired other countries to review their policies.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Single Convention on Narcotic Drugs of 1961; Convention on Psychotropic Substances of 1971; United Nations Convention Against Illicit Traffic in Narcotic Drugs and Psychotropic Substances of 1988